Peran Profesi Kependidikan dalam Membangun Nilai-Nilai Karakter Mahasiswa Calon Guru Madrasah Ibtidaiyah - Affandi, Rizky Hasan; Panjaitan, Azhari; Novaliza , Aidelia; Aidin, Winda; Salsabina S., Laila; Sholeha , Dini; Nasution, Inom (Yayasan Pendidikan Islam Akmalia, 2022)
Teachers are role models for students to instill moral values ​​from an early age, ethics and standards in the practice of their duties, even at every beat of life, become indicators in education and teaching. As a means to prepare future teachers with character. Efforts to apply the character values ​​of future teachers emerge through higher education and vocational education. Teachers are not expected to only provide knowledge but also to provide examples of behavior that will serve as guides for students and their surroundings. A teacher who has a professional spirit is a teacher who has opinions, attitudes, always thinks, works seriously, works hard, full time, has great loyalty and is full of dedication to complete the work that is his responsibility. The task of teachers for national education must have great intelligence. but now teachers must have a gentle soul, good character in instruction, education and advocating for the ideals of the nation's children. Here the role of education personnel is needed in building the character values ​​of prospective teachers. So that prospective teachers can have the understanding and ability to develop professional roles as teachers with reference to professional attitudes and insight into the teacher's code of ethics in carrying out their duties.